(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Oral Lichen planus (OLP) is chronic mucocutaneous disorder with or without involvement skin, of unknown etiology. Lichen planus (LP) is T-cell-mediated chronic inflammatory disease of the stratified squamous epithelium. It can affect oral mucosa, skin, esophagus, nasal mucosa, larynx, genitalia, urinary tract, hair follicles and the eyes. Latterly has been focused on presence association between OLP and hepatitis C virus (HCV) infection, but this relation is not stable, since the prevalence of this virus in patients varies depended on studies, ranging from 0% to 67.8%. Objective:This study was established to investigate the relationship between the OLP and HCV infection in Iraq and to detect the virus by Real-time polymerase chain reaction (RT-PCR). Methods: Blood samples were collected from 62 patients with OLP and controls to detect the HCV in those patients by using one step anti-HCV test, ELISA test and RT-PCR. Results:The current study revealed that the early detection of HCV by one step Anti-HCV for all OLP patients was negative and by ELISA showed that four patients (12.5%) of OLP were positive for HCV. While using RT-PCR found that only one patient (3.1%) was positive for the presence of the virus. Conclusion:There was not relationship found between OLP and HCV infection in Iraqi patients. Keywords: Oral lichen planus, HCV, RT-PCR, ELISA DOI: 10.22578/IJMS.14.4.4